Studies on Antifungal Activity and Brine Shrimp Toxicity Argemone mexicana (KYAMC Journal, 2017)
The present study determined the antifungal activity of the root of extracts Argemone mexicana against 7 fungi using dichloromethane and methanol as solvent. Among these pathogens, 3 were dermatophytes and the rest 4 were nondermatophytes. The dichloromethane extract of Argemone mexicana exhibited moderate to good activity at concentration of 200 ?g/disc but at concentration of 50 ?g/disc, the same extract showed no activity against the tested fungi. The methanol extract were also inactive against the tested pathogens. In brine shrimp toxicity test, it was observed that LC50 value of the dichloromethane extract of Argemone mexicana was 22.35 ?g/ml. From these findings it is indicative that dichloromethane extract of Argemone mexicana is biologically active and may have antifungal principles that could be useful in fungal diseases.KYAMC Journal Vol. 4, No.-2, Jan 2014, Page 402-405